Sistem Inventori menggunakan Metode Periodic Inventory System dengan Database Firebird 2.0 - Faisal Rahman; Firman Aziz; Dhilan Sasmita (Journal of System and Computer Engineering (JSCE), 2022)
This inventory system is very important for the company, especially at PT. Sinar Home Shopping which is engaged in the distribution or sale of goods and the availability of goods in fulfilling orders. But inventory problems are often an obstacle in having to go in and out of goods. Where in the company PT. Sinar Home Shopping goods data processing is still done manually starting from reports on goods, suppliers, customers, sales reports and purchase reports. so errors often occur. Therefore, the problem of the author's company conducting research to design an inventory system for PT. Sinar Home Shopping by using Delphi 2010 Embarcadero and Firebird 2.0 which is the best solution to overcome this in this case helping to simplify and speed up work in processing data recapitulation of goods, suppliers, customer sales and purchase transactions and make it easier to find information. The results obtained are the system can provide accurate data quickly and can facilitate users in calculations and reports.